Global research trends in bioherbicides for sustainable weed management: A bibliometric analysis (1981–2025) - Furkan Ulaş; Hilmi Torun; Muhammad Aasim; Khawar Jabran; Hüsrev Mennan (Phytoparasitica, 2026)
Bioherbicides have gained increasing attention as sustainable alternatives to synthetic herbicides in modern weed management. This study presents a comprehensive bibliometric analysis of global bioherbicide research published between 1981 and 2025 using data retrieved from the Web of Science Core Collection. A total of 992 publications were analysed using VOSviewer (version 1.6.20) and the Biblioshiny interface of the Bibliometrix package in RStudio to evaluate publication trends, citation patterns, collaboration networks, thematic evolution, and conceptual structures within the field. The retrieved publications accumulated 18,123 citations and achieved an H-index of 56, indicating considerable scientific impact and sustained scholarly influence. Publication output remained limited before 2000 but increased markedly after 2010, reaching peak productivity after 2020. Keyword co-occurrence analysis identified 117 keywords grouped into 10 clusters, with a total of 974 links and a total link strength (TLS) of 2273, revealing a highly interconnected conceptual structure centred around microbial biological control, allelopathy, natural products, sustainability, and integrated weed management. Thematic evolution and Multiple Correspondence Analysis (MCA) demonstrated a progressive transition from early pathogen-based and allelopathic studies toward interdisciplinary approaches integrating sustainable agriculture, molecular research, and bioactive natural compounds. The United States, Canada, and Italy emerged as the leading contributors, while institutions such as the USDA played central roles within international collaboration networks. Despite substantial scientific progress, major challenges related to formulation technologies, environmental stability, field-level consistency, regulatory constraints, and commercialization continue to limit large-scale adoption of bioherbicides. Emerging interdisciplinary approaches, including artificial intelligence-assisted discovery approaches, metabolomics integration, and advanced formulation technologies, may further support the future development of sustainable bioherbicide research and application.